Patient Prosthesis Mismatch After SAVR and TAVR - Bleiziffer, Sabine; Rudolph, Tanja K. (Frontiers in Cardiovascular Medicine, 2022)
Patient-prosthesis mismatch (PPM) remains one out of many factors to be considered during decision-making for the treatment of aortic valve pathologies. The idea of adequate sizing of a prosthetic heart valve was established by Rahimtoola who published „The problem of valve prosthesis-patient mismatch“ in Circulation in 1978[1]. In his article, he described the phenomenon, that the orifice area of a prosthetic heart valve may be too small for the individual patient. PPM is assessed by measurement or projection of the prosthetic effective orifice area indexed to body surface area (iEOA), while it is recommended to use different cut point values for non-obese and obese patients for categorization of moderate and severe PPM. Various of factors influence the accuracy of both the projected and the measured iEOA for PPM assessment, which leads to a certain number of false assignments to the PPM or no PPM group. Despite divergent findings on the impact of PPM on clinical outcomes, there is consensus that PPM should be avoided to prevent sequelae of increased prosthetic gradients after aortic valve replacement. To prevent PPM, it is required to anticipate the iEOA of the prosthesis prior to the procedure. The use of adequate reference tables, derived from echocardiographically measured mean EOA values from preferably large numbers of patients, is most appropriate to predict the iEOA. Such tables should be used also for transcatheter heart valves in the future. During the decision-making process, all available options should be taken into account for the individual patient. If the predicted size and type of a surgical prosthesis cannot be implanted, additional surgical procedures such as annular enlargement with the Manougian technique, or alternative procedures such as transcatheter aortic valve implantation can prevent PPM. PPM prevention for TAVR patients is a new field of interest and includes anticipation of the iEOA, prosthesis selection and procedural strategies.